Fodor's Puerto Rico 2025 - Mercado, Adriana; Ruiz, Jennifer (Fodor's Travel, 2025)
"Whether you want to stroll the atmospheric streets of Old San Juan, lounge on the island's beautiful beaches, or escape to Vieques or Culebra, the local Fodor's travel experts in Puerto Rico are here to help! Fodor's Puerto Rico guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time."--Publisher.